Faktor-Faktor yang mempengaruhi Purchase Intention - Pebanji, Pebanji; Sutrisno, Nuno (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2023)
The purpose of this study was to determine the effect of Price, Product, Promotion, Place, Cultural Influence, Social Influence, Personal Influence, and Psychological Influence on Purchase Intention of Wardah Lipstick Product in DKI Jakarta. The research method used in this research is through a survey. The data analysis was done quantitatively and used a casual research design. The sampling method used in this study is to use Non-Probability Sampling with purposive sampling technique. All sample data obtained by distributing questionnaires totaled 136 respondents and will be processed using SPSS 25 software. The data analysis technique used in this study is multiple linear regression. The results of this study indicate that Social Influence, Personal Influence, and Psychological Influence have an influence on Purchase Intention. But Price, Product, Promotion, Place and Culture Influence have no significant impact on Purchase Intention. This research is expected to provide input or suggestions to cosmetics companies especially Wardah Cosmetic on their Lipstick Products which is the object of this research, is to be able to increase its competitiveness and market share in cosmetic products in Indonesia.